Akurasi Antara Isi Siaran Pers Dengan Pemberitaan Media Online Nasional Periode 2018 (Analisis Isi Siaran Pers Dpp Organda) - Hardian, Arvin (Komunika: Journal of Communication Science and Islamic Dakwah, 2018)
The method used by quantitative content analysis authors, where the authors analyze the contents of the press release of the Central Board of Land Transport Organizations (DPP ORGANDA) period 2018 related to online media coverage calculated quantitatively for each frequency distribution of each research material based on title type categories. lead type category, 5W + 1H completeness category in content, and news value element category. The sample in the study was determined based on matching between press releases and news published by national online media, each 10 (ten) samples. The research coder consisted of two online journalists and one staff member at Organda DPP, who were given research material, coding sheets, and definitions of the same category. The coding results in a reliability coefficient of 0.88 (80%). Based on the results of the study, the suitability of the Organda DPP press release was obtained with the news loaded from the title type category by 80%, the lead type category by 60%, the 5W + 1H element completeness category by 80%, the news value element category by 90%. The discussion, it can be concluded that if public relations practitioners have the skills to write a press release, pay attention to the rules and basic patterns of press release writing, and write press releases like journalists write news, then it is likely that the press release can be published in mass media, especially the media national online which is also supported by media relations that is well established.